Idiopathic thrombocytopenic purpura. Clinical case - V. V. Syvolap; Ye. V. Novikov; O. G. Onishko (Zaporožskij Medicinskij Žurnal)
Aim. To draw the attention of physicians - internists to the problem of thrombocytopenia and hemorrhagic vasculitis. To describe the clinical case of idiopathic thrombocytopenic purpura, features of diagnostics and treatment of this disease at various stages of medical care, to highlight some aspects of the epidemiology, pathogenesis, modern diagnostics and treatment of disease.